SISTEM PENERIMAAN CALON MAHASISWA BARU DENGAN MENGGUNAKAN APLIKASI LOGIKA FUZZY PADA MATLAB TOOLBOX - Wulandari, Aisyah Ayu; Yusuf, Miftakhudin; Utami, Vi Bauty Riska; Permana, Yoga Adi (Universitas Komputer Indonesia, 2020)
In this era, education is a crucial thing, one of which is a tertiary institution. At a tertiary institution to be able to enter one of the tertiary institutions, there is a process in it that contains a series of activities ranging from registration, selection based on standards made and acceptance. In this process, to facilitate a process in determining the prospective new students by the needs requires a long process and consideration for that, we need a system to facilitate the selection process. Fuzzy logic is a methodology of problem-solving control systems that can be implemented on a system. The application of the new student admission system modeling using independent lane logic applications. This modeling is used as a system to solve or simplify a problem. In making a system modeling, a method like the Mamdani method is needed. Mamdani method is often known as the max-min method. In the Mamdani method, there are several stages, namely determining the fuzzy set, the implication function implications, the composition of the rules, and defuzzication. In this modeling using a fuzzy set of Scholastic Potential Test (TPS) and Academic Competency Test (TKA) variables. The magnitude of the value of the two variables is very influential on the output results that determine whether the prospective new student is accepted, considered, or rejected. From the modeling of this system, it can be concluded that by making modeling of this system can simplify and shorten the selection process of new students just by filling in the input values ​​in the modeling of the system and will get definite results. Key Words : Fuzzy, Student, Mamdani